DEVELOPMENT OF STUDENT WORKSHEET BASED PQ4R ON CHEMICAL BOND MATERIALS CLASS X HIGH SCHOOL - Poppy Andaeri; Asmadi M Noer; Roza Linda (Universitas Negeri Surabaya, 2020)
The purpose of this study is to develop PQ4R-based LKPD in high school chemistry learning subject to valid chemical bonds based on aspects of content eligibility, PQ4R characteristics, linguistic, presentation and graphic as well as knowing user responses to LKPD. This type of research is development research with the development process referring to the development of the Plomp model. Consists of the initial investigation, design, realization / construction, test, evaluation and revision, and implementation phases. However, this research is limited only to the test, evaluation and revision phases because the purpose of this study is to develop the product and determine the user's response. The object of this research is PQ4R-based LKPD. Data collection instruments are validation sheets and user responses. The results of the data analysis obtained validity on the aspects of content eligibility, PQ4R characteristics, linguistic, presentation and graphic characteristics, respectively; 97.62%, 95.24%, 91.67%, 95.24%, and 91.67% with valid categories. Trial of user responses by teachers and students in a row; 95.83% and 91.63%, so the LKPD that has been developed is suitable for use in the learning process.